Preventive Treatments of Iron Deficiency Anaemia in Pregnancy: A Review of Their Effectiveness and Implications for Health System Strengthening - Kayode O. Osungbade; Adeolu O. Oladunjoye (Hindawi Limited, 2012)
Objectives. We conducted a review of effectiveness of preventive treatments of iron deficiency anaemia in pregnancy in developing countries and highlighted their constraints as well as interventions required to strengthen the health services. Methods. Literature from Pubmed (MEDLINE), AJOL, Google Scholar, and Cochrane database was reviewed. Results. Evidence-based preventive treatment options for iron deficiency anaemia in pregnancy include prophylaxis iron supplements and food fortification with iron. Evidence abounds on their effectiveness in reducing the prevalence of iron deficiency anaemia in pregnancy. However, these prospects are threatened by side effects of iron supplements, low utilization of maternal health service in developing countries, partial implementation of preventive treatments, and weak infrastructure and political commitment to implement mass fortification of local staple foods by national governments. Conclusion. Sustainability of effectiveness of preventive treatments of iron deficiency anaemia in pregnancy could be achieved if the identified threats are adequately addressed.